2021
DOI: 10.1029/2020ea001466
|View full text |Cite
|
Sign up to set email alerts
|

What Can We Know About Recent Past Precipitation Over Africa? Daily Characteristics of African Precipitation From a Large Ensemble of Observational Products for Model Evaluation

Abstract: Over the past decades, Africa has been affected by significant rainfall anomalies: for instance, both the Horn of Africa and West Africa suffered severe droughts during the 1970s and 1980s (e.g., Williams et al., 2012) and, recently, the City of Cape Town in South Africa was hit by one of the worst multi-year droughts in decades (Otto et al., 2018). On the other hand, severe floods have affected countries located in dry areas, such as Algeria, Tunisia, Egypt, and Somalia (Niang et al., 2014).The analysis and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 71 publications
1
29
0
Order By: Relevance
“…Notably, Rx1day shows the largest discrepancy between modelled and observed results, and the largest uncertainty amongst COR-DEX simulations. This is particularly true for the western Sahel, where Dosio et al (2021a) showed that half of the CORDEX results are outside the range of uncertainty of a large ensemble of observational products.…”
Section: Precipitation Indicesmentioning
confidence: 99%
See 3 more Smart Citations
“…Notably, Rx1day shows the largest discrepancy between modelled and observed results, and the largest uncertainty amongst COR-DEX simulations. This is particularly true for the western Sahel, where Dosio et al (2021a) showed that half of the CORDEX results are outside the range of uncertainty of a large ensemble of observational products.…”
Section: Precipitation Indicesmentioning
confidence: 99%
“…As discussed by many studies (Ayugi et al 2019;Hua et al 2019;Dinku et al 2018;Gebrechorkos et al 2019;Maidment et al 2015;Nicholson et al 2018;Harrison et al 2019;Dosio et al 2021a), estimates of the observed recent climatology are very uncertain over Africa especially for regions where gauge networks are sparse (e.g. central Africa).…”
Section: Observational Datasetmentioning
confidence: 99%
See 2 more Smart Citations
“…This illustrates that the agreement of the observations is less than that of the model simulations (see Fig. 5f and, e.g., Dosio et al, 2021b). Interestingly, CORE shows the largest overestimation of R20mm than CMIP5 and CMIP6 over the Orange basin (all basins) during DJF (MAM and SON, except for Zambezi during MAM).…”
Section: Spatial Distribution Of Biasesmentioning
confidence: 73%